2014
DOI: 10.4014/jmb.1405.05016
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota of Tenebrio molitor and Their Response to Environmental Change

Abstract: A bacterial community analysis of the gut of Tenebrio molitor larvae was performed using pyrosequencing of the 16S rRNA gene. A predominance of genus Spiroplasma species in phylum Tenericutes was observed in the gut samples, but there was variation found in the community composition between T. molitor individuals. The gut bacteria community structure was not significantly affected by the presence of antibiotics or by the exposure of T. molitor larvae to a highly diverse soil bacteria community. A negative rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 29 publications
4
22
1
4
Order By: Relevance
“…Another study found that the three dominant bacterial phyla were Tenericutes (44.2%), Proteobacteria (39.22%) and Firmicutes (13.09%), and the genus Spiroplasma was the most abundant OTU (44.1%) [48]. A third study confirmed the dominance of Tenericutes (36.6%), Proteobacteria (34.1%), and Firmicutes (26.2%), and at the genus level also Spiroplasma (38.7%) [53]. Members of the genus Spiroplasma are small, helical, motile and wall-less bacteria [54].…”
Section: Microbial Contaminationsupporting
confidence: 49%
See 1 more Smart Citation
“…Another study found that the three dominant bacterial phyla were Tenericutes (44.2%), Proteobacteria (39.22%) and Firmicutes (13.09%), and the genus Spiroplasma was the most abundant OTU (44.1%) [48]. A third study confirmed the dominance of Tenericutes (36.6%), Proteobacteria (34.1%), and Firmicutes (26.2%), and at the genus level also Spiroplasma (38.7%) [53]. Members of the genus Spiroplasma are small, helical, motile and wall-less bacteria [54].…”
Section: Microbial Contaminationsupporting
confidence: 49%
“…The microbiota of the mealworm beetle is vulnerable to antibiotics, which reduce the bacterial diversity as well as the bacterial load, but it is stable against environmental factors [53]. Furthermore, sterile mealworms perform poorly, suggesting that the microbiota is required for the efficient digestion and detoxification of plant secondary products [76].…”
Section: Antibiotic Usementioning
confidence: 99%
“…Also, some Spiroplasma spp. known as insect pathogen effects on the larvae of T. confusum without causing any harm (Jung et al, 2014). Although it is difficult to know which microbial genera or families are responsible for the degradation of polystyrene because only a few degrading bacteria have been isolated.…”
Section: Resultsmentioning
confidence: 99%
“…The remarkable findings of of the ability of mealworm in extracting PHAs granules has led to this study. Mealworms are omnivorous insects that can grow on low‐quality feeds such as organic wastes . They can survive on P. mendocina PSU cells that were cultivated in MSM medium containing BLW.…”
Section: Discussionmentioning
confidence: 99%